2019
DOI: 10.2355/isijinternational.isijint-2018-816
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analyses of Chemical Structural Change and Gas Generation Profile of Coal upon Heating toward Gaining New Insights for Coal Pyrolysis Chemistry

Abstract: Chemical structure of coal is evolutionary changed during pyrolysis that accompanies gas release. The chemical structural change and gas formation profiles play important roles in determining caking property and physical properties such as strength and size of the resultant coke. However, analyses of volatile components and structural analysis of solid char have been mostly performed individually, and it is difficult to combine both and to obtain quantitative understanding on the thermal decomposition of coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Coal contains small molecules with Mw of 200-500; 14) some of these molecules have a naphthalene structure (two aromatic rings), 15,16) which can enhance the softening and melting properties of coal. 17) Considering the purpose of this study, the model compound was required to be solid at room temperature and liquid during heating; it was also required to have a boiling point of approximately 500°C.…”
Section: Requirements and Synthesis Scheme For Model Compoundmentioning
confidence: 99%
“…Coal contains small molecules with Mw of 200-500; 14) some of these molecules have a naphthalene structure (two aromatic rings), 15,16) which can enhance the softening and melting properties of coal. 17) Considering the purpose of this study, the model compound was required to be solid at room temperature and liquid during heating; it was also required to have a boiling point of approximately 500°C.…”
Section: Requirements and Synthesis Scheme For Model Compoundmentioning
confidence: 99%
“…The experimental apparatus and measurement conditions were provided in the previous studies. 6,9) In brief, a raw sample placed on a combusting boat in a horizontal tubular reactor was heated at the same rate for the char preparation in an Ar flow of 200 mL/min. The volatiles produced from the pyrolysis of the sample were introduced to the Q-MS through a depressurized capillary column at 25 mbar after removing large condensable molecules at a quartz wool layer and two cold traps.…”
Section: Online Measurement Of Gas Evolution Duringmentioning
confidence: 99%
“…[1][2][3][4][5] The authors have proposed a novel method for evaluating transferable hydrogen based on online measurement of the gas product during coal pyrolysis and spectroscopic analysis of the heat-treated char without mixing hydrogen acceptor additives to eliminate the fear of side reactions. 6) In this study, to extend the applicability of the method proposed in the previous study, we investigated three typical types of coal, namely, bituminous, sub-bituminous, and lignite coal, which are classified into high-rank, low-tomoderate rank, and low-rank coal, respectively. The path of hydrogen was tracked based on gaseous pyrolysis products and the chemical structure of solid products.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars studied the evolution of chemical structure of coal during pyrolysis and found that the structure of semi-coke is the main factor affecting combustion performance. Wang et al , analyzed the pyrolysis characteristics of coal through experimental research. Zhao et al proved through experiments that the synergistic effect of physical mixed co-pyrolysis has an obvious effect on the pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…Taking lignite and corn straw as the research objects, they studied the feasibility of catalytic reforming of the co-pyrolysis volatiles of three iron ores. Tetsuya Fukuoka et al analyzed the solid chemical structure and gaseous distribution of coal under two same pyrolysis conditions, which supplemented the coal pyrolysis (CP) mechanism. Mishra et al , revealed the evolution path of coal structure pyrolysis reaction at different temperatures and thus proposed the devolatilization mechanism of chemical structure evolution in coal high temperature pyrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%